Narratology in Gina Prince-Bythewood’s Film - The Woman King - Charles Obot; Ubong Andem Obong (CV. Rayyan Dwi Bharata, 2023)
This work was concerned with narratology in Prince-Bythewood’s (2022, 02:14:49) film, The Woman King. It was specifically set to analyse the narrative structure inherent in the film. In doing this, the researchers formulated four research objectives to guide the narrative analysis of the film. The objectives were to: describe how the plot is structured to enhance the film narrative; explain how the director established dramatic elements such as setting, conflict, and denouement in enhancing the film narrative; critically examine the metaphorical and literary themes that help to enhance the film narrative; and to discuss how the director’s use of cinematography enhance the film narrative. The theoretical underpinning of the Narrative Theory provided explications to the narratological exegesis attempted in the study. The study, using the qualitative content analysis and narratology methodologies, described and critically analysed Prince-Bythewood’s (2022, 02:14:49) deployment of narratives and narrative structures in the story (plot) and discourse from settings; dramatic twists; themes (metaphorical and literary); dramatic conflict/climax; denouement; and other cinematographic elements such as visual effects; stunts; lighting and lighting effect; non-linear editing; sound and sound effect; and languages of dramatic dialogue.